2020
DOI: 10.3389/fonc.2020.541330
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Stromal Score Signature: Novel Prognostic Tool of the Tumor Microenvironment in Lung Adenocarcinoma

Abstract: Background: Immune and stromal cells in the tumor microenvironment (TME) significantly contribute to the prognosis of lung adenocarcinoma; however, the TME-related immune prognostic signature is unknown. The aim of this study was to develop a novel immune prognostic model of the TME in lung adenocarcinoma. Methods: First, the immune and stromal scores among lung adenocarcinoma patients were determined using the ESTIMATE algorithm in accordance with The Cancer Genome Atlas (TCGA) database. Differentially expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…The stromal and immune scores are measures of the proportion of stromal and immune cells in the tumor tissue, respectively, and the ESTIMATE score indicate tumor purity, which is defined as the percentage of tumor cells in the TME and is closely related to the prognosis of cancer. The findings showed a significant correlation between risk scores and all three of these other factors, possibly predicting an effect of the TME on lymph node metastasis (Qi et al, 2020). Tumor-infiltrating B cells are a key component of adaptive immunity, and data on the antitumor effects of B cells in NSCLC are inconsistent (Hu et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…The stromal and immune scores are measures of the proportion of stromal and immune cells in the tumor tissue, respectively, and the ESTIMATE score indicate tumor purity, which is defined as the percentage of tumor cells in the TME and is closely related to the prognosis of cancer. The findings showed a significant correlation between risk scores and all three of these other factors, possibly predicting an effect of the TME on lymph node metastasis (Qi et al, 2020). Tumor-infiltrating B cells are a key component of adaptive immunity, and data on the antitumor effects of B cells in NSCLC are inconsistent (Hu et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…TME consists of surrounding cells and noncellular components. Tumor-infiltrating stromal cells and immune cells as the major cell components of surrounding cells that play a significant role in cancer prognosis [9][10][11]. For example, Vigano et al found that tumor-infiltrating lymphocytes and macrophages were associated with prognosis in intrahepatic cholangiocellular carcinoma patients after complete surgery [12].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence suggested that tumor microenvironment (TME) which is composed of tumor cells, immune cells, stromal cells, inflammatory mediators and extracellular matrix [ 2 ], taking part in the tumor progression and drug resistance [ 3 , 4 ]. Among them, immune cells and inflammatory mediators have been proved to be valuable for the prognostic of LUAD [ 5 ]. Much attention has been paid on the immune microenvironment of LUAD.…”
Section: Introductionmentioning
confidence: 99%